Mechanistic insights into 5-aminolevulinic acid photodynamic therapy for acne vulgaris: targeting lipogenesis via the OLR1-Wnt/β-catenin pathway - Jia Yan; Linglin Zhang; Qingyu Zeng; Yitao Qian; Ke Li; Xiaojing Liu; Yun Wu; Yu Yan; Haiyan Zhang; Szeman Cheung; Jia Liu; Ronald Sroka; et al. (Molecular Medicine)
Abstract Acne vulgaris, a prevalent chronic inflammatory skin disorder, is often characterized by hyperactive sebaceous glands and excessive sebum production, presenting a significant therapeutic challenge. While 5-aminolevulinic acid photodynamic therapy (ALA-PDT) is clinically effective in treating moderate to severe acne, the molecular mechanisms underlying its therapeutic effects remain largely unexplored. In this study, we investigated the impact of ALA-PDT on lipid metabolism in an acne-like mouse model and in immortalized human sebocytes (XL-i-20), focusing on the role of the OLR1-Wnt/β-catenin pathway. We employed transcriptomic analysis, lipid staining, and gene silencing techniques to dissect the molecular interactions induced by ALA-PDT. Our findings revealed that ALA-PDT significantly reduces lipogenesis by upregulating OLR1, which in turn suppresses the SREBP1-FAS axis, thereby decreasing lipid accumulation in sebocytes. Furthermore, activation of the OLR1-Wnt/β-catenin pathway was essential for these lipogenic effects, as silencing OLR1 or activating Wnt/β-catenin signaling reversed lipogenesis inhibition. This study elucidates a novel mechanistic pathway in ALA-PDT-mediated acne treatment, highlighting OLR1 as a promising target for future therapeutic strategies.